Study of Surrogate Immunohistochemical Markers IDH1, ATRX, BRAF V600E, and p53 Mutation in Astrocytic and Oligodendroglial Tumors - Santosh Sharma; Kusum Mathur; Alka Mittal; Meel Mukta; Arpita Jindal; Mukesh Kumar (Indian Journal of Neurosurgery, 2023)
Introduction In consonance with current the World Health Organization (WHO) classification of the central nervous system (CNS) tumors (2016), histological diagnosis of gliomas should be reinforced by molecular information. This study was performed to determine the frequency of isocitrate dehydrogenase 1 (IDH1), α thalassemia/intellectual disability syndrome X-linked (ATRX), p53, and BRAF V600E mutations in different grade astrocytomas and oligodendrogliomas.